Thaddäus Zielinski im Lichte seiner Autobiographie - Schröder, Wilt Aden (Hyperboreus, 2016)
Subsequent to his university education in Germany (mainly in Leipzig) and more than three decades as a lecturer and professor at the university of Saint Petersburg, the eminent polish philologist Thaddäus Zielinski (1859–1944) emigrated to Poland shortly after the Russian revolution. During his time in Warsaw, where he assumed a professorship at the recently reconstituted university, he composed a highly self-conﬁdent autobiography addressed to his children in 1924. Based on additional sources, this paper examines some of his claims, his position in Russian society and his relations with scholars in Russia.